2023
DOI: 10.3390/su15065100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Content in Wheat Straw Biochar on N2O and CO2 Emissions and Pakchoi Productivity Under Different Soil Moisture Conditions

Abstract: Agricultural soils are a primary source of greenhouse gas (GHG) emissions. Biochar is commonly used as a soil amendment to prevent climate change by reducing GHG production, increasing soil carbon storage, improving soil moisture retention, and enhancing crop productivity. However, the impact of biochar’s carbon content under subsurface drip irrigation (SDI) has not been well studied. Here, we investigated the effect of different carbon (C) contents in wheat biochar under different SDI depths on soil nitrous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…The most significant reduction was seen in soils amended with sugarcane straw biochar, where N2O emissions were 50% lower than in NF (Figure 12 B). This finding corroborates with studies that have observed suppression of N2O emissions caused by straw-based biochars (Abbruzzini et al, 2019;Hamad et al, 2023;Zhang et al, 2022). Conversely to previous studies that reported no reductions in soil N2O emissions in response to woody biochar application (Lan et al, 2019;Ramlow et al, 2019), we observed that both wood-based biochars reduced N2O emissions.…”
Section: Discussionsupporting
confidence: 92%
“…The most significant reduction was seen in soils amended with sugarcane straw biochar, where N2O emissions were 50% lower than in NF (Figure 12 B). This finding corroborates with studies that have observed suppression of N2O emissions caused by straw-based biochars (Abbruzzini et al, 2019;Hamad et al, 2023;Zhang et al, 2022). Conversely to previous studies that reported no reductions in soil N2O emissions in response to woody biochar application (Lan et al, 2019;Ramlow et al, 2019), we observed that both wood-based biochars reduced N2O emissions.…”
Section: Discussionsupporting
confidence: 92%
“…Irrigation is the leading water resource consumer and a key factor affecting soil greenhouse gas emissions [ 1 ]. Irrigation can change the conditions of soil moisture, temperature, oxygen, and microorganisms, thus influencing the production and release of greenhouse gases such as carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is a serious global issue due to increasing environmental pollution and the fast expansion of agricultural lands. Gaseous carbon emissions are released continuously into the atmosphere [1]. The carbon cycle in agroecosystems is the most fundamental ecological process and has a crucial impact on greenhouse gas emissions such as CO 2 and CH 4 [2].…”
Section: Introductionmentioning
confidence: 99%
“…The carbon cycle in agroecosystems is the most fundamental ecological process and has a crucial impact on greenhouse gas emissions such as CO 2 and CH 4 [2]. At the 75th United Nations General Congress [1], China proposed that its carbon dioxide emissions would reach a peak by 2030 and it would achieve carbon neutrality by 2060. Therefore, it is urgent to increase crop production by paying more attention to reducing greenhouse gas emissions and increasing their sequestration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation